MEMBACA DAN MENULIS PERMULAAN: PERAN ORANG TUA DALAM MEMPERSIAPKAN ANAK MENUJU PENDIDIKAN DASAR DI PAUD SAFITRI KECAMATAN SERANG - Risna, Inten; Andini, Andini; Rianti, Rini; Hasanah, Hasanah; Anisah, Anisah; Sumarni, Ani; Fitriyani, Fifi; Rusdianti, Shofia (Yayasan Education and Social Center, 2025)
This community service activity aims to provide parents with an understanding of the importance of early literacy and effective ways to stimulate the reading and writing skills of young children. The theme of the activity is